Facilitating Multi-Stakeholder Dialogue and Collaboration in the Energy Transition of Municipalities through Serious Gaming - Tania Ouariachi (Energies, 2021)
Within the EU, energy transition at the local level is embedded in a complex stakeholder network with highly interdependent actors; if these actors have to collaborate to contribute to an efficient transition, they have to initiate a dialogue about their roles and interests. A good way to achieve this goal could be via serious gaming. Scholars suggest that serious games have the potential to increase multi-stakeholder’s dialogue and collaboration on climate-change-related issues; however, empirical evidence on the effectiveness, and the process is still limited. The aim of this paper is to use the We-Energy Game as a case study to provide empirical evidence on how serious gaming could facilitate dialogue and collaboration among different stakeholders, and which specific features influence the engagement of participants with the issue. For that purpose, a qualitative analysis on feedback and observations of group discussions is conducted, together with a survey for 125 stakeholders from diverse municipalities in The Netherlands to assess what type of features influence the engagement. The study reveals that the game engages participants mostly at the cognitive level, and that key elements in this process are game design, the debriefing session, and the role of the facilitator.